Adolescent Substance Use Disorder Diagnosis Correlates With Hospitalization After an Emergency Department Visit. Issue 10 (6th October 2022) - Thurstone, Christian; Loh, Ryan; Piatz, Christopher; Simpson, Scott A.
Abstract : Introduction: The purpose of this study is to compare the prevalence of hospitalization after an emergency department (ED) visit at an urban safety net hospital for youth with and without a substance use disorder. Methods: This study used a retrospective cohort design of adolescents (aged 15–21 y; n = 14, 852) treated in the ED and compared the risk of hospitalization within 90 days. Results: A substance use disorder diagnosis in the ED more than doubled the risk of 90-day hospitalization (5.4% vs 2.38%; P < 0.0001). Conclusions: Compared with youth without a substance use disorder, youth with substance use disorders are likely to require additional services after an ED visit.